2015
DOI: 10.1103/physrevx.5.021019
|View full text |Cite
|
Sign up to set email alerts
|

Colossal Proximity Effect in a Superconducting Triplet Spin Valve Based on the Half-Metallic FerromagnetCrO2

Abstract: Combining superconductors (S) and ferromagnets (F) offers the opportunity to create a new class of superconducting spintronic devices. In particular, the S=F interface can be specifically engineered to convert singlet Cooper pairs to spin-polarized triplet Cooper pairs. The efficiency of this process can be studied using a so-called triplet spin valve (TSV), which is composed of two F layers and a S layer. When the magnetizations in the two F layers are not collinear, singlet pairs are drained from the S layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
151
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(180 citation statements)
references
References 24 publications
22
151
2
5
Order By: Relevance
“…Half-metallic (H) ferromagnets (already employed in various superconducting hybrid structures, see, e.g., Refs. [12,13]) should lead to highly efficient splitting due to absolute spin filtering. At the same time, mutual orientation of magnetizations in the two arms can, in principle, be varied continuously by weak external magnetic field if one of the arms is exchange biased (a scheme similar to, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Half-metallic (H) ferromagnets (already employed in various superconducting hybrid structures, see, e.g., Refs. [12,13]) should lead to highly efficient splitting due to absolute spin filtering. At the same time, mutual orientation of magnetizations in the two arms can, in principle, be varied continuously by weak external magnetic field if one of the arms is exchange biased (a scheme similar to, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Those groups found evidence for spin-triplet generation occurring during the magnetization reversal process while sweeping an external magnetic field. Better control of the magnetic states has been achieved recently by several groups measuring the critical temperature T c of S/F/F trilayers, where generation of spin-triplet correlations results in lowering of T c [21][22][23][24][25][26]. Controlling T c , however, is less likely to be useful for future device applications than controlling supercurrent.…”
mentioning
confidence: 99%
“…Very recently, Singh et al reported [9] the observation of a colossal triplet spin-valve effect for the S/F1/N/F2 structure made of amorphous MoGe, Ni, Cu, and CrO 2 as the S, F1, N, and F2 layers, respectively. This structure demonstrated variation of T c by ∼ 1 K when changing the relative alignment of the two F layers.…”
mentioning
confidence: 99%